2014
DOI: 10.1039/c4qo00295d
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric cobalt catalysts for hydroboration of 1,1-disubstituted alkenes

Abstract: The chiral iminopyridine oxazoline (IPO) ligands were designed, synthesized and utilized for the first cobalt-catalyzed highly regio-and enantioselective anti-Markovnikov hydroboration of 1,1-disubstituted aryl alkenes. This novel IPO ligands will likely be of high value for asymmetric transformations with first-row transition metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(62 citation statements)
references
References 46 publications
1
61
0
Order By: Relevance
“…We elected to investigate the visible‐light promoted hydroboration of alkenes: an atom‐economical, value‐adding transformation which has provoked substantial research. Examples of both Markovnikov and anti‐Markovnikov cobalt‐catalysed hydroborations have been reported previously. Many of these examples, however, rely on complex ligand systems or use an air sensitive cobalt complex that must be manipulated in a glovebox .…”
Section: Methodsmentioning
confidence: 90%
“…We elected to investigate the visible‐light promoted hydroboration of alkenes: an atom‐economical, value‐adding transformation which has provoked substantial research. Examples of both Markovnikov and anti‐Markovnikov cobalt‐catalysed hydroborations have been reported previously. Many of these examples, however, rely on complex ligand systems or use an air sensitive cobalt complex that must be manipulated in a glovebox .…”
Section: Methodsmentioning
confidence: 90%
“…More interestingly,t he a-vinylsilanes react with pinacolborane (HBpin) to form geminal borosilanes 10 with excellent regioselectivity.T he formation of the sterically crowded tetrasubstituted carbon center through Markovnikov hydroboration is remarkable because Lu and co-workers [19] and our group [10g] previously demonstrated that IPO Co precatalyst 3a gave exclusively the anti-Markovnikov hydroboration products when 1,1-disubstituted aryl alkyl alkenes were used as the substrates.Incontrast, acatalyst screen revealed that the Co and Fe complexes of IPO (3a, 3b), PDI (5a, 5b), and Pybox (6a, 6b)w ere all selective for the formation of geminal borosilane 10 a in the reaction of 2a with HBpin (see the Supporting Information). Among them, PDI Co complex 5a was most effective;i nt he presence of this precatalyst (2 mol %) and NaBHEt 3 (4 mol %), 10 a was formed in 90 % yield.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Although cobalt complexes have been reported to catalyze the hydroboration of alkenes, under the optimized conditions, allenes exhibit a much higher reactivity than both terminal and internal alkenes as demonstrated by the formation of Z ‐ 4 q , Z ‐ 4 r , and Z ‐ 4 s in high yields with exclusive chemoselectivity.…”
Section: Methodsmentioning
confidence: 99%